PSIM: a crop scheduling simulation - Mattingly, Sue Silver, author; Basham, Charles W., advisor (Colorado State University. Libraries, 1979)
PSIM is a simulation model of raw product supply for a commercial pea canning operation. The primary purpose of the computer model is generation of planting and harvest schedules based on the heat unit system for predicting crop maturation. The simulation will schedule up to 30 plantings, each consisting of 20 subplantings, for as many as ten cultivars. Output includes a planting schedule, a table of projected harvest dates based on historical temperature data, final harvest dates based on a current year's temperature data, and yield figures. Maturity and yield are treated as stochastic elements in the model and samples are taken from normal distributions for both characteristics. Model rationale is presented along with a program listing, technical and user documentation. The heat unit system itself is examined in a review of the literature.
Covers not scanned.
Keywords: Peas; Cropping systems -- Simulation methods